The effect of season and fertilizer on the LAI, the photosynthesis and the yield of the maize hybrids with different genetic characteristics - El Hallof, Nóra; Sárvári, Mihály (Acta Agraria Debreceniensis, 2006)
The experiment was carried out in Debrecen, at the Experimental Station of the University of Debrecen Centre of Agricultural Sciences, Department of Crop Production and Applied Ecology. We tested 10 various hybrids with their own genetic characteristics for five different fertilizer doses, in addition to the parcels without fertilization. The three factors of production technology jointly determine the successfully of maize production, but in different measure. The yield and the stability of yield of maize can be increased with hybrid-specific technologies.In 2004-2005 experiment years the favorable results reached were due to the rainy season. There were significant difference between the productivity of maize hybrids. The N 40, P2O5 25, K2O 30 kg/ha treatment caused the highest increase of yield (3-5 t/ha) compared to the control (parcels without fertilization). The reaction of hybrids to the further fertilizer doses was different. The agro-ecological optimum of NPK fertilization was N 120, P 75, K 90 kg of the most hybrids.During the experiment, we tested the moisture loss of the five hybrids. The seed moisture content at harvest was higher than in previous years due to the rainy seasons. The seed moisture content of harvest of FAO 200-300 hybrids were about 20%. It changed between 21-24% in the case of hybrids with longer vegetation period (FAO 400), the seed moisture content of Mv Vilma (FAO 510) was 24.21-25.04% in the average of fertilizer treatments. There is an important difference between the moisture loss ability of hybrids which changed 0.2-0.6%/day. The moisture loss of hybrids changed depending on the fertilizer treatment; usually, it was more favorable in the optimal fertilizer dose (N120+PK).In the case of tested hybrids, we measured the highest LAI and photosynthetic activity at the optimal treatment, N 120, P2O5 75, K2O 90 kg/ha in the respect of efficiency and environmental protection, and the yield was high also for this treatment. There are significant difference between the LAI, the photosynthetic activity and the yield of hybrids, and these values could change depending on the treatment of fertilization.